A Rare Form of Melanoma Masquerading as a Diabetic Foot Ulcer: A Case Report. (4th April 2012) - Thomas, Susan; Meng, Yuan-Xiang; Patel, Vijaykumar G.; Strayhorn, Gregory
Abstract : Background . Acral lentiginous melanoma (ALM) is a less-common form of melanoma in US, and it accounts for about 5% of all diagnosed melanomas in US. ALM is often overlooked until it is well advanced because of the lesion's location and its atypical appearance in the early stages. We present a case of ALM initially presented as a diabetic foot ulcer. Case Report . An 81-year-old man initially presented to the primary care clinic with a right foot diabetic ulcer. There was a large plantar, dark-colored ulcer that bled easy. Initial excision biopsy revealed Clark's Level IV ALM. Subsequent definitive wide excision and sentinel node biopsy confirmed ALM with metastasis to inguinal lymph nodes (stage IIIb). The treatment included wide margin excision of the lesion with en bloc amputations of 4th and 5th toes, followed by adjuvant chemotherapy. Discussion . The development of ALM may potentially relate to diabetes as a reported higher prevalence of diabetes with ALM patients. Conclusion . The difficulty in early diagnosing of ALM remains as a formidable challenge particularly in diabetic patients who commonly develop plantar foot ulcers due to the diabetic neuropathy. This case reiterates the importance of a thorough foot exam in such patients.